2018 annual dialysis data report of the JSDT Renal Data Registry: patients with hepatitis - Kosaku Nitta (Renal Replacement Therapy, 2021)
Abstract According to the annual survey of the Japanese Society for Dialysis Therapy Renal Data Registry (JRDR) conducted at the end of 2018, a total of 339,841 patients were receiving dialysis (hereinafter, dialysis patients) in Japan. This survey included an investigation of individual test results for hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV) antibody (HCV-Ab), HCV-RNA, and serum alanine aminotransferase (ALT) (glutamic pyruvic transaminase [GPT]). The survey revealed that among dialysis patients in Japan, the prevalence of HBsAg positivity was 1.38% and the prevalence of HCV-Ab positivity was 4.7% at the end of 2018, both of which were markedly lower than the corresponding rates documented in 2007 (9.8% and 4.7%, respectively). The proportion of HCV-RNA-positive patients among all HCV-Ab-positive patients was 37.5%, which was also markedly lower than the percentage recorded in 2007 (64.0%). The prevalence of HBsAg positivity tended to increase as the dialysis vintage increased. The prevalence of HCV-Ab positivity was also not correlated with the dialysis vintage during the first 30 years of dialysis; however, it tended to increase as the dialysis vintage increased beyond the 30th year. Trial registration University hospital Medical Information Network (UMIN) Clinical Trials Registry, UMIN000018641 . The JRDR was approved by the ethics committee of the JSDT (approval number 1-3) and was registered on August 8, 2015 (accessed June 2, 2020).